2007
DOI: 10.1002/ajmg.b.30647
|View full text |Cite
|
Sign up to set email alerts
|

A twin study of the common vulnerability between heightened sensitivity to hypercapnia and panic disorder

Abstract: For unknown reasons the inhalation of CO(2)-enriched air mixtures evokes acute panic-like symptoms in people with panic disorder and in their unaffected relatives. This study was set to determine whether, and to what extent, CO(2)-induced acute anxiety and panic disorder share the same genetic and environmental determinants. Cholesky structural equation models were used to decompose into genetic and environmental elements the correlation between self-assessed anxiety post-35%CO(2)-65%O(2) inhalation and interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 47 publications
5
54
0
Order By: Relevance
“…To our knowledge, this is the first study investigating temperament and character dimensions in a sample of children at high risk for PD, and thus the results should be considered preliminary; we confirm the results of the two previous studies showing no differences in AS between children of patients with PD and those of healthy controls [23,24]. Our findings are in line with previous studies showing that CO 2 hypersensitivity, a familial vulnerability marker for PD with relevant heritable aspects [17,18,19,20], is related neither with temperamental dimensions [4] nor with AS levels [29,30]. Moreover, previous studies suggest that high AS or peculiar temperamental dimensions may be related with a large spectrum of anxiety symptoms or disorders [5,6,7,16], whereas hypersensitivity to CO 2 is specifically linked to panic vulnerability [31,32].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…To our knowledge, this is the first study investigating temperament and character dimensions in a sample of children at high risk for PD, and thus the results should be considered preliminary; we confirm the results of the two previous studies showing no differences in AS between children of patients with PD and those of healthy controls [23,24]. Our findings are in line with previous studies showing that CO 2 hypersensitivity, a familial vulnerability marker for PD with relevant heritable aspects [17,18,19,20], is related neither with temperamental dimensions [4] nor with AS levels [29,30]. Moreover, previous studies suggest that high AS or peculiar temperamental dimensions may be related with a large spectrum of anxiety symptoms or disorders [5,6,7,16], whereas hypersensitivity to CO 2 is specifically linked to panic vulnerability [31,32].…”
Section: Discussionsupporting
confidence: 82%
“…Family studies suggest that PD runs in families, with a relevant genetic source of the familial risk [1], and that hypersensitivity to CO 2 challenges represents a vulnerability marker for PD in both adult and children first-degree relatives of patients suffering from PD [17,18]. Finally, heritable aspects of CO 2 hypersensitivity and PD seem to overlap significantly [19,20]. Given that both temperament and AS have hereditary components [21,22] and may be linked to the vulnerability to PD, offspring of patients with PD might have peculiar temperament profiles or higher AS.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, the percentage of ‘anxiety-prone’ subjects amongst the 712 twins who underwent the 35% CO 2 /65% O 2 challenge was 20.5%, as compared to 13.5% prevalence in the original NIPHTP MHS sample. The subjects who accepted to participate in the CO 2 study did not differ from those in the original NIPHTP MHS sample for age and frequency of contact with the cotwin [21,22,28]. Moreover, preliminary analyses showed that the frequency of contact with the cotwin, did not influence the post-CO 2 response: regression summary R 2 = 0.001, F 2, 255 = 0.32, p = 0.97; telephone contact: β = –0.006, p = 0.94; personal contact: β = 0.018, p = 0.81.…”
Section: Methodsmentioning
confidence: 99%
“…While individual differences in the anxious reaction to CO 2 are moderately heritable, environmental factors explain a sizable proportion of variance [21,22] for post-CO 2 subjective anxiety. However, no study has so far been carried out to clarify whether AE predict the response to the CO 2 stimulation per se (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Human studies show that SAD predicts heightened risk to develop PD in adulthood (75,76) and both these conditions are associated with heightened sensitivity to CO 2 (44,77,78). In turn, CO 2 hypersensitivity shares common genetic determinants with both SAD and PD, with childhood parental loss adding a significant contribution to explain covariation (44).…”
Section: Endophenotype Levelmentioning
confidence: 99%